Book Review: Cooper, John F. Taiwan Nation-State or Province? Boulder: Westview Press, 2009. 288 PP. - Rivai, Ardian Bakhtiar (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
This article aims to describe about my analysis of Cooper (2009) perspective in how we understand Taiwan as identity. There are two perspective that to see Taiwan in recent day. First of all, for nation who believe One China Policy, they assume that Taiwan is a province of People Republic of China which is Taiwan is part of Beijing government. Secondly, for nation who do not believe it, they assume that Taiwan is independence identity, a nation identity, and also sovereign country which is separated from mainland China influences. In this discourse about how we understand Taiwan,  this article is going to review from John F. Cooper which is in his book, Taiwan: nation state or province?. This book not only discuss how we can see Taiwan, however, how Taiwan in the future in political dynamic especially after US president Donald Trump who intent to support Taiwan as independence identity.